The factors influencing postoperative efficacy of anterior clinoidal meningioma treatment and an analysis of best-suited surgical strategies - Chen, Li-Hua; Xia, Yong; Wei, Fan; Sun, Kai; Huang, Hong-Zhi; Xu, Ru-Xiang (Frontiers in Neurology, 2023)
Objective To explore the influence of the type of anterior clinoidal meningioma on surgical strategy planning, surgical approach selection, and postoperative efficacy. Patients and methods We conducted a retrospective analysis of the clinical data of 63 cases, including data on visual function, extent of tumor resection, and postoperative follow-up. Grade I and II approaches were selected according to the type of tumor. A univariate analysis of the factors influencing the extent of tumor resection, postoperative visual function, and postoperative relapse and complications was conducted. Results Simpson Grade I–II total resection was seen in 48 cases (76.2%), with an overall relapse/progression rate of 12.7%. The tumor type and texture and the relationship between the tumors and adjacent structures were the main factors influencing total tumor resection (P < 0.01). The overall postoperative visual acuity improvement, stabilization rate, and deterioration rate were 76.2, 15.9, and 7.9%, respectively. Postoperative visual acuity level was significantly correlated with preoperative visual acuity level and tumor type (P < 0.01). Conclusions Determining the type of tumor at a preoperative level and whether the optic canal and cavernous sinus are invaded can aid in the planning of detailed individualized surgical strategies.